The solution to the Puzzle of Archbishop Athanasius’ Portraits or on their Attribution Once Again - Milchik, Mikhail I. (Actual Problems of Theory and History of Art, 2013)
The article examines the provenance and attribution problem of portraits of Archbishop Kholmogorsky and Vazhsky Athanasius (1641–1702). The author adduces evidence of the following attribution: 1) “grave portrait” of archbishop (not preserved) which was painted by S. Narykov and known by its representation on the photos; 2)”Portrait in black mantle” (1701) is its copy by I. Pogorelsky made during archibisop’s lifetime; 3) ”Portrait in red mantle” is a late copy.
Keywords: archbishop Kholmogorsky and Vazhsky Athanasius; Russian portrait of early 18th c; S. Narykov; I. Pogorelsky